Association between cognitive function and Cre/BW in middle-aged and older Chinese adults: evidence from the CHARLS - Shuting Li; Mengya Qi; Yanxue Wang; Xingmeng Lu; Xingang Li (Frontiers in Public Health)
BackgroundCre/BW has been widely validated as a reliable biomarker for assessing muscle mass in clinical and epidemiological studies. Accumulating evidence from longitudinal cohort studies has demonstrated a significant association between sarcopenia and progressive cognitive decline in aging populations. To further elucidate this relationship, we conducted a comprehensive analysis using data from a nationally representative survey.MethodsThis study utilized longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS), with baseline measurements collected in 2012 and follow-up assessments conducted in 2018. To comprehensively evaluate the association between Cre/BW and cognitive function, we employed a dual analytical approach. Cross-sectional analyses were performed using multivariable-adjusted linear regression models for continuous cognitive scores and logistic regression models for dichotomous cognitive outcomes. For longitudinal assessment, we implemented time-to-event analyses using Cox proportional hazards models, with rigorous adjustment for potential confounders including demographic characteristics, lifestyle factors, and comorbidities.ResultsInitial unadjusted linear regression analysis revealed a significant inverse association between Cre/BW ratio and total cognitive function score (β = −0.111, 95% CI: −0.013 to −0.008, p < 0.001). This association remained statistically significant after comprehensive adjustment for potential confounders, albeit with attenuated effect size (β = −0.052, 95% CI: −0.007 to −0.003, p < 0.001). When analyzing cognitive function scores by quartiles, we observed a consistent pattern where lower Cre/BW ratios were associated with better cognitive performance, even after multivariable adjustment (OR = 0.973, 95% CI: 0.951 to 0.996, p = 0.019). Longitudinal analysis using Cox proportional hazards models demonstrated that higher Cre/BW ratios were significantly associated with increased risk of cognitive impairment (HR = 1.207, 95% CI: 1.073 to 1.359, p = 0.002). Notably, participants in the highest Cre/BW quartile showed a 1.118-fold increased risk of cognitive impairment compared to those in the lowest quartile (95% CI: 1.048 to 1.346, p = 0.007), suggesting a dose–response relationship between Cre/BW ratio and cognitive outcomes.ConclusionOur findings demonstrate a significant inverse association between Cre/BW and cognitive function in the general Chinese adult population. Longitudinal analysis revealed that elevated Cre/BW ratio serves as an independent risk factor for cognitive impairment, with this association persisting after extended follow-up and comprehensive adjustment for potential confounding factors.